Comparative effectiveness of silodosin vs. tamsulosin in treating acute urinary retention in benign prostatic hyperplasia patients - Hassan-Ul-Hassan; Tanzeel-Ur-Rahman Gazder; khan, Nawaz; Jafri, Abbas; Hassan, Asad Shahzad; Hashmi, Altaf (Journal of the Pakistan Medical Association, 2025)
Objective: To evaluate the effectiveness of silodosin and tamsulosin in patients with acute urine retention caused by benign prostatic hyperplasia. Method: The prospective cohort study was conducted at the Sindh Institute of Urology and Transplantation, Karachi, from July to December 2022, and comprised male benign prostatic hyperplasia patients with acute urine retention. The patients were divided into group A receiving 0.4mg tamsulosin and group B receiving 8mg silodosin. The catheter was withdrawn after seven days. Trial without catheterisation success was measured by patients’ post-void residue. All patients were reassessed for post-void residue at 4 weeks after a successful trial without catheterisation. Data was analysed using SPSS 21. Results: Of the 130 male subjects with mean age 64.79±9.71 years, mean prostate volume 46.22±6.82ml and mean post-void residual 96±13ml on day 7 and 89.73±14.38ml on day 28, 65(50%) were in each of the two groups. Intergroup difference with respect to efficacy at four weeks was not significant (p=0.584). Conclusion: The efficacy of tamsulosin and silodosin in individuals with benign prostatic hyperplasia was comparable. Key Words: Acute urinary retention, Benign prostatic hyperplasia, Trial without catheter, Tamsulosin, Silodosin, Lower urinary tract symptoms.